Pendampingan Penyusunan Modul Ajar Kurikulum Merdeka Bagi Guru PJOK Kota Semarang - Buyung Kusumawardhana; Maftukin Hudah; Fajar Ari Widiyatmoko; Ibnu Fatkhu Royana; David Firna Setyawan; Pandu Kresnapati; Danang Aji Setyawan (Universitas PGRI Semarang, 2022)
The independent curriculum on the independent learning platform has been launched. There are not a few teachers who are not ready and have sufficient understanding to implement it, including PJOK teachers in SMA Kota Semarang where the PJOK subjects phase E (grade 10) and phase F (grades 11-12) do not yet have a flow of learning objectives and teaching modules. This PkM activity aims to provide assistance in technical guidance instilling an understanding of the independent curriculum, identifying learning outcomes, learning objectives (ATP), and Teaching Modules. The methods used are lectures, discussions, training and mentoring. Participants in the activity were PJOK SMA Semarang teachers, totaling 75 people. The results of the activity showed an increase in teacher motivation and understanding as well as the ability to develop independent curriculum teaching tools.Kurikulum merdeka dalam platform merdeka belajar telah diluncurkan. Tidak sedikit guru yang belum siap dan memiliki pemahaman yang memadai untuk mengimplementasikannya, termasuk juga guru PJOK di SMA Kota Semarang dimana mata pelajaran PJOK fase E (kelas 10) dan fase F (kelas 11-12) belum tersedia alur tujuan pembelajaran dan modul ajarnya. Kegiatan PkM ini bertujuan untuk memberikan pendampingan dalam bimbingan teknik penanaman pemahaman kurikulum merdeka, mengidentifikasi capaian pembelajaran, alur tujuan pemnbelajaran (ATP), dan Modul Ajar. Metode yang digunakan ceramah, diskusi, pelatihan dan pendampingan. Peserta kegiatan adalah guru-guru PJOK SMA Kota Semarang yang berjumlah 75 orang. Hasil kegiatan menunjukkan adanya peningkatan motivasi dan pemahaman serta kemampuan guru dalam menyusun perangkat ajar kurikulum merdeka.